Microbial content of bioaerosols in outdoor urban recreation areas of an Atlantic coastal city (Fortaleza-CE, Brazil - Cajazeiras, Ítalo Magno Pereira (2022)
Introduction: Regular physical activity and outdoor leisure provide significant health benefits. In urban environments, issues related to the air microbiological quality have become a priority due to the pandemic situation we are experiencing. This study analyzed the aerial microbiota of outdoor public spaces, using a qualitative and quantitative approach in Brazilian coastal town. Materials and methods: Three intra-urban areas were analyzed and characterizing according the thermo-hydrometric characteristics and vegetal cover. Bioaerosols were collected during the wet and dry seasons using the passive sampling technique with selective growth media for fungi and bacteria. Microbial groups were quantified on agar plates; colonies were randomly selected, purified and classified. The antibiotic resistance was evaluated against 6 antibiotics belonging to 6 classes. Results: Bacteria were relatively more frequent than fungi in the three areas. Among isolates, bacteria represented from 76% (P1) to 90% (P3) of the suspended microbiota in the rainy season; in dry season, the percentages varied from 87% (P1) to 91% (P2 and P3). Genus Bacillus was the main representative of Gram positive and Enterobacter genus the most frequently identified among Gram-negative bacteria. Aspergillus and Penicillium genera were the dominant among fungi. Fifty per cent from bacterial strains analyzed were resistant to at least one of the tested antimicrobials. Conclusion: Bacteria proved more abundant than fungi and more susceptible to climate and environmental changes in the leisure areas of the city. The monitoring of biological agents in the air is important for environmental management and population health.